The concept, features, and types of procedural decisions in criminal proceedings - Pchelina, O. V. (Аналітично-порівняльне правознавство, 2025)
In the article it has been that reforming the institution of criminal proceedings must involve not only improving the formal mechanisms for decision-making but also ensuring that this process is infused with a focus on human rights, the principles of the rule of law, adversarial proceedings, proportionality, and predictability. The necessity of addressing current challenges has been highlighted, including the integration of digital technologies into the work of pre-trial investigation bodies, enhancement of mechanisms for protecting the rights of victims – especially vulnerable individuals – and the adaptation of best European practices. An analysis of the current state of scientific development on the subject has been carried out, noting the diversity of approaches to defining the essence of procedural decisions. Special attention has been given to the definition of procedural decisions in legislation, in particular, an analysis of Part 1 of Article 110 of the Criminal Procedure Code of Ukraine. The article provides a thorough review of existing scholarly approaches to understanding the essence, content, form, and structure of procedural decisions. The author proposes their own justification for the further systematization of this legal category to form an effective, fair, and humane system of criminal justice that meets the modern demands and challenges of society. Procedural decisions in criminal proceedings have been defined as individual legal acts adopted by authorized entities in a statutory procedural form, aimed at resolving issues arising during criminal proceedings which result in the emergence, modification, or termination of the legal rights and obligations of their participants, create procedural consequences, guarantee a balance between the public interests of the state and the protection of human rights, are mandatory for execution, and may be enforced by the state if necessary. Types of procedural decisions in criminal proceedings have been distinguished by adopting entity, procedural act form, stage of criminal proceedings, legal consequences, content and direction, and method of adoption.